MAINSET REVOLUTION: RELATIONSHIPS AND PARTICIPATION FOR THE KINGDOM OF GOD - Arip Supri Sitompul; Sarjani Jojor Martua Sianturi; Jon Roi Tua Purba; Kepler Sianturi; Novalina S Silaban (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Awareness of the Kingdom of God demands a holistic transformation within the lives of believers. This transformation encompasses not only the spiritual dimension but also the renewal of mindset and practical actions that align with Gospel values. This study, entitled "Mindset Revolution: Relationship and Participation for the Kingdom of God", seeks to explore the theological significance of transforming the mindset of believers as a key foundation for realizing the Kingdom of God on earth. The research employs a qualitative method with a theological-biblical approach, drawing on literature review, biblical text analysis, and critical engagement with contextual theological works. The findings reveal three main points. First, synchronizing the human mindset with divine wisdom requires the renewal of the mind and a paradigm shift from an ego-centered to a theocentric orientation, grounded in love, truth, and divine justice. Second, the relationship between God, humanity, and the world is understood as an interconnected framework, where God is the source of life, humanity is called to be both partner and steward of creation, and the world serves as the arena for the actualization of the Kingdom of God. Third, human participation is realized in three dimensions: personal (faithfulness and holiness of life), social (solidarity and justice), and ecological (preservation and restoration of creation). In conclusion, the mindset revolution is not merely a theoretical concept but a transformative and practical movement that calls for active participation of believers in manifesting the Kingdom of God within social, moral, and ecological realities.